2009
DOI: 10.1007/s10509-009-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

Dust acoustic solitary waves in dusty plasma with nonthermal ions

Abstract: In this paper, the characteristics of the dust acoustic solitary waves in dusty plasmas are studied. The distribution of ions is nonthermal, and the nonthermal parameter is treated as a variable. The pseudo-potential method has been used to investigate the possibility of soliton formation. We show that for some values of the nonthermal parameter there is no soliton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
(19 reference statements)
1
20
0
Order By: Relevance
“…6 indicate that a decrease of the fractional number density of the hot electrons relative to that of the cold ones number density (α = n h0 /n c0 → 0) would lead to an increase of the depth as well as the width of the localized electron-acoustic solitary wave. Our findings are in good agreement with recently published results (Pakzad 2009a(Pakzad , 2009b(Pakzad , 2010Alinejad 2010aAlinejad , 2010b, in the sense that a departure from thermodynamic equilibrium not only affects the salient features of the localized solitary structures but also modifies the domain of their admissible Mach numbers.…”
Section: Theoretical Model and Basic Equationssupporting
confidence: 93%
“…6 indicate that a decrease of the fractional number density of the hot electrons relative to that of the cold ones number density (α = n h0 /n c0 → 0) would lead to an increase of the depth as well as the width of the localized electron-acoustic solitary wave. Our findings are in good agreement with recently published results (Pakzad 2009a(Pakzad , 2009b(Pakzad , 2010Alinejad 2010aAlinejad , 2010b, in the sense that a departure from thermodynamic equilibrium not only affects the salient features of the localized solitary structures but also modifies the domain of their admissible Mach numbers.…”
Section: Theoretical Model and Basic Equationssupporting
confidence: 93%
“…In a recent paper Pakzad (2009) studied the occurrence of large-amplitude solitary waves in a dusty plasma with cold negatively charged dust, nonthermal positive ions and Boltzmann distributed electrons, using a Sagdeev pseudopotential method. He discussed the influence of the parameters characterizing the degree of nonthermality, the ion-to-electron temperature ratio and the relative species' densities on the existence domains where negative solitary waves can occur.…”
Section: Dear Editormentioning
confidence: 99%
“…He discussed the influence of the parameters characterizing the degree of nonthermality, the ion-to-electron temperature ratio and the relative species' densities on the existence domains where negative solitary waves can occur. The main result claimed by Pakzad (2009) seems to be that for some values of the nonthermality parameter the minimum and maximum Mach numbers coincide, which prevents the existence of negative solitary wave solutions. The possibility that there might be positive solitary structures was not mentioned nor investigated.…”
Section: Dear Editormentioning
confidence: 99%
“…Exact pseudo-potential derived from analytical form and numerical solution have shown that the nonthermal distribution modified solitary waves (Chatterjee and Roychaudhury 1995;Cairns et al 1995a). For some values of the nonthermal parameter there is no soliton (Pakzad 2009). The ion temperature changes the minimum value of the nonthermal parameter as well as the Mach number for the coexistence of compressive and rarefactive ion-acoustic solitary waves (Mamun 1997).…”
Section: Introductionmentioning
confidence: 99%